An Evaluation on İlmiye Studies in the 100th Anniversary of the Republic - Mehmet İpşirli (Tarih Dergisi)
In the Ottoman Empire, the ilmiye, represented by the ulema, held educational, judicial, and major religious institutions within the state structure, and in the periods of establishment and development, they mostly held the posts of vizier and minister. The ilmiye is a group of people with important privileges and at the forefront of state ceremonies. Studies on this important institution -especially on its educational aspects- began to be conducted in the Republican period, starting in the 1940s. Since the 1960s, interest has gradually increased as the ilmiye started to be taught as a course in history departments, and related doctoral theses began to emerge. The situation during the 100th anniversary of the Republic shows that many theses, articles, and books have been written and symposiums have been organized on various topics of ilmiye. However, many important topics have not yet been examined, and no standardized work has yet been written in the field of ilmiye after Uzunçarşılı’s book.